2020
DOI: 10.17645/up.v5i3.2918
|View full text |Cite
|
Sign up to set email alerts
|

Urban Arrival Infrastructures between Political and Humanitarian Support: The ‘Refugee Welcome’ Mo(ve)ment Revisited

Abstract: <p>Maximilian Park in Brussels was the site of a makeshift refugee camp for three months in 2015 when the institutional reception system was unable to provide shelter for newly arriving asylum seekers. Local volunteers stepped in, formed a civic initiative and organized a reception area under the banner ‘Refugees Welcome!’ The civic platform which emerged claimed and asserted (existing) rights for one specific group, asylum seekers, exclusively, and thus did not challenge the exclusive migration regime n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This research is part of a continuous academic engagement with the Plateforme Citoyenne 4 and the Maximilianpark in Brussels since the informal refugee camp was established in 2015 (see Saltiel, 2020Saltiel, , 2021. In 2020, the focus of the empirical research turned to Hébergement.…”
Section: Methods a Caring Research Encounter?mentioning
confidence: 99%
See 2 more Smart Citations
“…This research is part of a continuous academic engagement with the Plateforme Citoyenne 4 and the Maximilianpark in Brussels since the informal refugee camp was established in 2015 (see Saltiel, 2020Saltiel, , 2021. In 2020, the focus of the empirical research turned to Hébergement.…”
Section: Methods a Caring Research Encounter?mentioning
confidence: 99%
“…More recent critical research, however, shows that encounters alone do not necessarily lead to changes in preconceptions and prejudices nor to greater respect or solidarity-too often, underlying unequal relations of power 1 Maximilianpark is situated in the Northern Quarter in Brussels next to the Foreigners' Office where asylum applications are processed, and right in front of the Brussels North station. For the meaning of Maximilianpark as the space of arrival in Brussels, see Saltiel (2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By choosing 'the poorest' to be eligible for (and assumed to be dependent on) generous care services, humanitarian care ethics reproduce the prevailing politics of need interpretation (Ticktin 2006). 'Refugees Welcome' initiatives often fail to challenge the mechanisms that produce difference and inequality (Saltiel 2020; van Dyk and Misbach 2016) and rather reinstate the hierarchical dialectic of 'generous citizens' as caregivers and 'victimized passive immigrants' as care receivers. It is observed that voluntary work with refugees is often ascribed to a so-called "racism of help" (Byakuleka and Ulu 2016: 18, own translation) that in the act of care (re)establishes relations that refer, at least implicitly, to racist stereotypes of 'white supremacy.'…”
Section: Humanitarian Care Ethics and Democracymentioning
confidence: 99%
“…However, they were excluded from receiving the services and moreover from the decision-making processes in the camp. This eventually led to severe conflicts between the Platform and some sans-papiers (see De Praetere and Oosterlynck 2017;Saltiel 2020).…”
Section: The Re-production Of Classificationsmentioning
confidence: 99%